HYDROGEN TECHNOLOGIES IN CONNECTION WITH NUCLEAR POWER PLANT - Avsec, Jurij (Journal of Energy Technology, 2024)
Efficient and sustainable methods of clean fuel production are needed in all countries of the world in the face of depleting oil reserves and the need to reduce carbon dioxide emissions. With commitments for a hydrogen village, a hydrogen airport and a hydrogen corridor, the Canadian province of Ontario has already begun to move toward a hydrogen-fuelled economy. However, a key missing element is a large-scale method of hydrogen production. As a carbon- based technology, the predominant existing process (steam-methane reforming (SMR)) is unsuitable. This paper focuses on a production of hydrogen in connection with a nuclear power plant. We will show the technologies which allow the coupling between a nuclear power plant and hydrogen technologies.